Concurrent SPECT/PET-CT imaging as a method for tracking adoptively transferred T-cells in vivo. Issue 1 (17th May 2016) - Stanton, Sasha E.; Eary, Janet F.; Marzbani, Edmond A.; Mankoff, David; Salazar, Lupe G.; Higgins, Doreen; Childs, Jennifer; Reichow, Jessica; Dang, Yushe; Disis, Mary L.
Abstract : Background: The ability of T-cells to traffic to and penetrate tumors impacts the clinical efficacy of T-cell therapy therefore methods to track transferred T-cells in vivo are needed. In this preliminary report, we evaluated the use of concurrent SPECT/PET-CT imaging to monitor the egress of HER-2/neu specific T-cells in a breast cancer patient with extensive bone-only metastatic disease. Findings: Indium (In-111) labeled T-cells demonstrated similar or greater viability than unlabeled T-cells at either a low or high dose of In-111 over a 24-h incubation period in vitro. The function of labeled or unlabeled T-cells was not significantly different ( p  > 0.05) at either dose. T-cells trafficked to all sites of metastatic disease and infiltrated the tumor as assessed by SPECT imaging. In-111 uptake at 24 h after infusion varied from 3.8 (right proximal humerus) to 6.3 (right sacrum) background corrected counts per pixel and remained elevated at 48 h. Concurrent PET-CT imaging demonstrated a fluorodeoxyglucose flare, measured by increase in tumor site uptake as high as 32 % and at most sites of disease at 48 h. This flare was associated with focal pain after T-cell infusion at metastatic sites. The patient had stable disease for 18 months after completion of T-cell therapy. Conclusion: Concurrent SPECT/PET-CT imaging, over a 48-h period after T-cell infusion, provided evidence of T-cell homing to all disease sites as well as a tumor metabolism flare response. This technique may be useful for monitoring T-cell trafficking after autologous as well as chimeric antigen receptor T-cell infusion. Trial Registraion: Trial registered at ClinicalTrials.gov registration number NCT00791037, registered 13 November 2008.